2019
DOI: 10.1111/jog.13917
|View full text |Cite
|
Sign up to set email alerts
|

Adverse symptoms during short‐term use of ulipristal acetate in women with uterine myomas and/or adenomyosis

Abstract: Aim To evaluate various adverse symptoms during short‐term use of ulipristal acetate in women with uterine myomas (n = 90), adenomyosis (n = 3) or both (n = 7). Methods One hundred premenopausal women who received ulipristal acetate for 4–12 weeks during 2016 to 2017 were selected. The medical records were reviewed and the following information was collected; adverse symptoms during medication, presence of menorrhagia or menstrual cramps, blood hemoglobin and liver function test. Adverse symptoms were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Uterine fibroids (UFs) are the most common neoplasms of the uterus and affect more than 70% of women of reproductive age (1). Of these women, 50 % of them are symptomatic and have complaints such as; vaginal bleeding, pelvic pain, pressure sensation, severe anemia and urethral obstruction (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Uterine fibroids (UFs) are the most common neoplasms of the uterus and affect more than 70% of women of reproductive age (1). Of these women, 50 % of them are symptomatic and have complaints such as; vaginal bleeding, pelvic pain, pressure sensation, severe anemia and urethral obstruction (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…No larger studies on pregnancy outcomes and only cases of pregnancy are reported after these procedures for adenomyosis. 35,36 At present, these techniques have, therefore, not been recommended for women with adenomyosis and a wish to conceive.…”
Section: Uterus-sparing Surgical Outcomesmentioning
confidence: 99%
“…Interestingly, UPA reduces AUB as effectively as the GnRH agonist Leuprorelin but without hypoestrogenic side effects ( 90 ). Some adverse effects associated with UPA treatment have been noted, such as weight gain and fatigue and recently potential concerns regarding negative liver effects have been highlighted ( 91 ).…”
Section: Emerging Treatmentsmentioning
confidence: 99%